'The Lynchpin of the Acute Stroke Service'—An envisioning of the scope and role of the advanced nurse practitioner in stroke care in a qualitative study. Issue 23 (18th October 2020) - Laird, Elizabeth Ann; McCauley, Claire; Ryan, Assumpta; Beattie, Alison
Abstract: Background: Stroke prevalence is rising internationally. Advanced practice nursing is established across many jurisdictions; however, its contribution to stroke services is under research. Aim: To gain insights into the future scope and role of future advanced nurse practitioners in stroke care from the perspectives of key stakeholders. Design: A qualitative descriptive approach. Methods: Interviews were conducted in 2019 with a purposive sample of 18 participants, comprising stroke nurses, stroke unit managers, stroke survivors and their family carers, recruited in one UK healthcare trust. The research is reported in line with COREQ. Data were analysed in accordance with an inductive content analysis approach. Results: The abstraction process generated four main themes. These were 'The lynchpin of the acute stroke service', 'An expert in stroke care', 'Person and family focussed' and 'Preparation for the role'. Conclusion: These findings offer new perspectives on the potential scope and role of advanced nurse practitioners in stroke service delivery. Further research should focus on how to address the challenges confronted by advanced nurse practitioners when endeavouring to engage in autonomous clinical decision‐making. Impact: Study findings may advance postregistration education curricula, clinical supervision models and research directions. Relevance to clinical practice: There is support for the implementation of advanced practice nursing in the hyperacute and acute stroke phases of the care pathway. An interprofessional model of clinical supervision has potential to support the developing advanced nurse practitioner in autonomous clinical decision‐making.